NILAI KARAKTER DISIPLIN SISWA MELALUI PELAJARAN IPS KELAS IX TINGKAT MTS - Dewi Nafila; Ninik Indawati; Cicilia Ika (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
The background to this research is because in an educational institution there are 3 main aspects that should be achieved by students in an educational institution, including affective, cognitive and psychomotor aspects. However, recently in educational institutions, especially those in remote areas, there has been a lot of focus on the cognitive aspect, without paying attention to other aspects, such as the affective aspect which is actually very important because it is related to student behavior as well as disciplinary attitudes. Based on this, there are four problems, namely: first, analysis of the value of students' discipline character through class IX social studies lessons at MTsN 3 Pamekasan; second, what is the condition of the disciplinary attitudes of class IX students. Third, how to instill discipline in students through social studies learning in class IXmekasan students, fourth, what are the obstacles for social studies teachers in instilling discipline in class IX students. The objectives of this research include: first, to analyze the value of students' discipline character through social studies lessons; second, to determine the condition of disciplinary attitudes of class IX students. Third, to determine the instillation of students' disciplinary attitudes through social studies learning, fourth, to identify the obstacles of social studies teachers in instilling disciplinary attitudes in class IX students at MTsN 3 Pamekasan. This research uses a qualitative approach with a descriptive type. The data sources were obtained through interviews, observation and also documentation. The informants were the school principal, social studies teacher, and class IX students at MTsN 3 Pamekasan. Meanwhile, checking the validity of the data is carried out through extending participation, increasing persistence and triangulation. The research results obtained are: (1) Analysis of the value of students' disciplined character through class IX social studies lessons, namely social studies learning activities become a benchmark in assessing how disciplined the students are, social studies learning is also always relevant in cultivating discipline, social studies learning covers 4 dimensions, one of which is values ​​and attitudes, so that the student's discipline character score is 80% of each class IX at MTsN 3 Pamekasan (2) The condition of the discipline attitude of class IX students is classified as good as evidenced by the majority of students complying with existing regulations. There are also students who are not disciplined, triggered by internal and external factors, 80% of students have behaved in a disciplined manner. (3) Instilling a disciplinary attitude in students through social studies learning, namely contextualizing social studies learning, innovative learning, getting used to it and carrying out counseling activities and exercising control over students, so that 90% have behaved in a disciplined manner (4) The obstacle for social studies teachers in instilling a disciplinary attitude is the teacher's lack of understanding related to the root of student problems, unconducive classroom conditions and the diversity of student abilities or 10% of the number of each class IX at MTsN 3 Pamekasan.